Climate Change Policy Options for Asian Economies : Findings from an Integrated Assessment Model - van der Mensbrugghe, Dominique (2012)
This study outlines potential futures for the global economy through the 2050 with a specific focus on the countries of Asia. With underlying assumptions about population and output growth, a baseline scenario assesses the growth of greenhouse gas emissions and the ensuing impacts on the climate. Under the baseline scenario, Asia's high growth leads to a strong rotation in global output and emissions by the year 2050. The analytical framework traces back the changes in temperature to economic damages--limited to the agricultural sectors. Parts of Asia are likely to see much higher dependence on food imports as a consequence of these damages. Various carbon tax scenarios are implemented to assess the potential for reducing carbon emissions. Because of the structure of their economies, Asian countries are likely to bear the greatest burden in reducing emissions in an efficient global tax scheme, but there is significant scope to ease this burden through financial transfers.